Microrganismos indutores de crescimento no desempenho de plantas de arroz irrigado tropical - Sousa, Israel Mendes (2019)
Rice is a staple food for the half of world population. It is rich source of carbohydrates, thus, represent important source of energy for the maintenance of human metabolism, mainly in underdeveloped and developing countries. Due to the population increases in rice consuming countries, it is estimated that by 2030 there should be an approximately 20% increase in rice production for supply the demand for this food. Plant growth promoting rhizobacteria (PGPR) and fungi of genera Trichoderma spp. are beneficial microorganisms, which, associated to plant species can induce the growth and hence increase crops production. Therefore, the use of plant growth inducing microorganisms represents an important alternative to improve vegetable species production and, ensure food security in a sustainable way. The aim of this work was to determinate the effect of kinds and forms of application of microorganisms in the agronomic performance of tropical lowland rice plants. Experiments were carried out in the completely randomized design (CRD), where, it was evaluated biomass production, physiological characteristics through gas exchanges, nutrient content in plants and, seedling root length of tropical lowland rice. The treatments were of six rhizobacteria isolates: BRM32109 e BRM32110 (Bacillus sp.); BRM32111 (Pseudomonas fluorescens); BRM32112 (Pseudomonas sp.); BRM32113 (Burkholderia pyrrocinia) e BRM32114 (Serratia sp.) and, one pool with four Trichoderma asperellum isolates (UFRA.T06 + UFRA.T09 + UFRA.T12 + UFRA.T52). Data were submitted of variance analyses and to means LSD’s test (p≤0.05). To compare treatments with microorganism and control plants the data were submitted to Dunnett’s test (p≤0.05). Based on results, it can be inferred that the use of beneficial microorganisms in tropical lowland rice plants may represent alternative to improve the crop yield. Overall, the application of beneficial microorganisms improved the performance of tropical lowland rice plants compared to control plants, through of higher biomass, gas exchange improvement, uptake nutrients and seedling root length. However, in the different experiments the behavior of microorganisms differed. It is know that the interaction between microorganisms and plants is dependent on some specifications, such as, vegetable specie/cultivar, soil kind, environmental conditions and concentration of microorganisms on the colonization region. Thus, beside of positive results, there is a need for further investigations of effect and mainly interaction of these different beneficial microorganisms in different lowland rice cultivars in field trials.